Citric acid acidification of wheat straw derived biochar for overcoming nutrient deficiency in alkaline calcareous soil (Case of Phosphorus) - Adil Mihoub (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Phosphorous fixation in soils is a serious concern worldwide, and biochar is gaining attention daily due to its potential benefits for improving the agronomic benefits of applied phosphorus. The present study aims to enhance understanding of the phosphorus transformation process in a deprived sandy soil following biochar amendments (no-acidified wheat straw biochar and chemically modified (acidification with 0.01 M C6H8O7) along with or without phosphorus at 250 mg kg−1. A 54-day pot experiment was conducted with two biochar levels of 4%, 8% (w/w), and control, and two phosphorus levels (without or with phosphorus). The results indicate that the integration of acidified wheat straw biochar with phosphorus resulted in increased available phosphorus in the soil. We conclude that incorporating acidified wheat straw biochar is a promising practice to potentially improve phosphorus availability in deprived soils. Further research is needed to explore site-specific phosphorus management for sustainable crop production.